?LEAD INDUCED STIMULATION IN THE ACTIVITIES OF PEROXIDASE AND IAA OXIDASE AND THEIR INFLUENCE ON THE GROWTH IN MUNGBEAN - RASHID, PARVEEN; MUKHERJI, S. (Biological Sciences - PJSIR, 1996)
Foliar application of lead applied in four differentconcentrations (1,4,7 and 10mM) and the control (0) at five growth stages (28, 35, 42, 49 and 56 DAS) of rnungbean resulted in increased activities of both peroxidase and IAA oxidase. Highest stimulation in peroxidase activity was recorded at 56 days after sowing (DAS) by 10 mM dose while IAA oxidase showed maximum activity at 35 DAS under same dose. Lead also caused growth inhibition of plants by decreasing plant height, dry weight of leaf, stem and five entire plants.The effect was pronounced towards higher concentrations of lead.